Application of WebSocket on Integration of E-Reporting Infrastructure (ERI) Applications with IoT - Usman Nurhasan (International Conference on Industrial Revolution for Polytechnic Education, 2021)
E-Reporting Infrastructure (ERI) is an application for monitoring and reporting damage to existing infrastructure on campus. The web-android-based application has been implemented by involving several user actors. Damage reports are the main data that is processed to produce a priority scale for corrective actions. The existing obstacle is the absence of real time monitoring related to the condition of the infrastructure, especially the electrical infrastructure. So to find out the current condition of a tool, a site survey must be carried out and reported through the application. The implementation and analysis of crash reports is an integration of ERI and IoT. The IoT used is Arduino Uno with a communication protocol using web socket. The use of web socket was chosen because it is able to provide full-duplex communication on the HTTP protocol which is suitable for application control and monitoring systems. Implementation of web socket by adding the Thread feature so that it can accommodate many clients on one server. Client is assumed to be an electronic device that will be monitored in real time. The results of the performance test show that to carry out a one-time process of controlling and monitoring the device, the time required is no more than 1 second with a 100% success percentage. There is a decrease in performance when a request is made of 200 requests per second or connected simultaneously. With the increasing number of requests and the number of connected clients, it will affect the Round Time Trip and requests that are able to be served by the system